Book Review on Antonio Moreno-Munoz; Neomar Giacomini; Energy Smart Appliances: Applications, Methodologies, and Challenges (2023)‏ - Mousa, Hossam H. H.; Mahmoud, Karar; Lehtonen, Matti (Peneliti Teknologi Teknik Indonesia, 2024)
Recently, the integration of new industrial technologies is significantly increased into the utility grid such as renewable energy sources (RESs), distributed energy resources (DERs), energy source systems (ESSs), electric vehicles (EVs), and multi-carrier energy systems (MESs). So, robust energy management strategies are required to regulate the power-exchange between the generations and end-users for improving the power system's reliability and stability and reducing the energy costs. Thus, the demand-side management (DSM) strategies and demand response (DR) programs are utilized to control the energy smart appliances for residential building which achieving by various strategies, required infrastructure, energy market signals, etc. Several textbooks and articles investigate this important topic. However, the book entitled “Antonio Moreno-Munoz; Neomar Giacomini; Energy Smart Appliances: Applications, Methodologies, and Challenges (2023)”, is the most recent prominent comprehensive reference for DSM strategies in smart grids. Hence, this article proposes a book review and discussion of its most important contributions to DSM strategies by dividing them into four main contributions. Which helps the reader in realizing the recent developments on DSM strategies based on this book’s contents.